Capital structure, pay structure and job termination - Jason Allen; James R. Thompson (Bank of Canada, 2016)
We develop a model to analyze the link between financial leverage, worker pay structure and the risk of job termination. Contrary to the conventional view, we show that even in the absence of any agency problem among workers, variable pay can be optimal despite workers being risk averse and firms risk neutral. We find that firms employing workers with safer projects (and lower probability of job termination) use more variable compensation, and that leverage is strictly increasing in the amount of variable pay. These two results lead to the main insight of the paper: the more likely it is that a worker is terminated, the lower a firm's leverage. We provide empirical support for these predictions with a novel data set of all Canadian financial brokers and dealers. In the context of our empirical analysis, the model provides a novel mechanism to help explain why high leverage and high amounts of variable pay may be pervasive in financial relative to non-financial institutions.
Keywords: G24; J33; 330; Financial institutions; Labour markets